Anterior clinoidal meningioma coincidental with bilateral intracranial aneurysms - Paraskevopoulos, D (LITHOGRAPHIA Antoniadis I.-Psarras Th. G.P., 2011)
Coexistence of aneurysms and brain tumors is a rare occurrence. Coincidence is highest in patients with meningiomas rather than other types of tumors. We report a case in which a meningioma of the left anterior clinoid process was coexisting with a right middle cerebral artery (MCA) and a left anterior cerebral artery (ACA) aneurysm. While the right MCA aneurysm was detected preoperatively, the left ACA aneurysm was not detectable, being concealed by the major finding of the region. This report focuses on pitfalls of diagnosis and questions the surgical planning in aneurysms concealed by coincidental brain tumors.